character in a novel I loved you more than i should (Journal of the College of Basic Education, 2022)
The novel (I loved you more than I should) is a novel with a large female dimension that constitutes a clear imprint in the Arab feminist novel art because it includes the elements of a successful novel experience, especially the personality element, the focus of the research. The character in the novel raises the problem of love and loyalty, belonging and non-affiliation, giving And denial, in an anti-oriental duality, is a syndrome for oriental women, as if it were a genetic imprint that she was born with.